The Role of Matrix Tablet in Oral Drug Delivery System - Yadav, Rajkumar Prasad; Sheeba, F. R.; Sharma, Mukesh; A, Bhargav; Kumar, Yaswanth; Patel, Akshay Kumar (Asian Journal of Pharmaceutical Research and Development, 2021)
Matrix tablet is an important tool for controlled and sustained release dosage forms. The important route of drug administered by oral route. The oral dosage forms developed and improvedthe patient compliance. The oral controlled release system has been developed by change to formulation scientist, due to the inability to restrain and localized of a system at target area of the gastrointestinal tract. The hydrophilic polymers are becomes product of choice for important ingredients formulation of sustained release dosage forms.The benefit of sustained release dosage forms are compared to the conventional dosage forms and uniform therapeutic effects and drug plasma concentration. The matrices used of various class of hydrophilic, hydrophobic, mineral or biodegradabletypes of polymers and their degradation product have been focused. The drug have less half-life and eliminated from the body with in short period of time. The formulation of drug matrix types have been avoided by difficult sustained release drug delivery system. The mechanism of matrix tablets include the both dissolution and diffusion controlled. It produce the therapeutic efficacy. The goal of this review article is to discuss the release mechanism of the drug dosage form of various polymers and a matrix system used in preparation of matrix tablets.